APLICAREA LEGII NR.165/2013 (PANGEEA, 2025)
The aplication of law no. 165/2013. The property right guaranteed by the Constitution, is one of the most important human rights, in modern society, according to Article No. 44 of the Constitution: "Private property is guaranteed and protected equally by the law, irrespective of its owner. "And" no one shall be expropriated except in the public interest, established by law, to just and prior compensation.